1999
DOI: 10.1002/1529-0131(199910)42:10<2189::aid-anr21>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective sleep disturbances in patients with systemic lupus erythematosus

Abstract: There is an enhanced presence of sleep disorders in patients with SLE. The most frequent primary sleep disorders are respiratory and movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
57
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 8 publications
12
57
4
1
Order By: Relevance
“…The use of prednisone in the present study was associated with sleep disturbances, although other studies have not shown a relationship between use of corticosteroids and sleep disturbance in SLE (4,5,32). Although fewer patients in our sample were receiving corticosteroids, a greater proportion were taking higher doses of corticosteroids compared with previous studies (4,5,32), which may partially explain our results.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The use of prednisone in the present study was associated with sleep disturbances, although other studies have not shown a relationship between use of corticosteroids and sleep disturbance in SLE (4,5,32). Although fewer patients in our sample were receiving corticosteroids, a greater proportion were taking higher doses of corticosteroids compared with previous studies (4,5,32), which may partially explain our results.…”
Section: Discussioncontrasting
confidence: 75%
“…A relationship between depressed mood and respiratory disturbances during sleep in SLE patients using polysomnographic data has previously been demonstrated (4). The relationship between sleep disturbances and depressed mood has also been shown in epidemiologic studies of sleep in the general population (33)(34)(35), and with other medical patients (i.e., arthritis, chronic pain) (36 -38).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Individuals with systemic lupus erythematosus (SLE) often contend with fatigue (1,2), pain (3), sleep disturbances (2,4), depression (1,3,5), and anxiety (6,7). Given the unpredictability of SLE, the severity of symptoms, and the fact that it affects young adults (8,9), a diminished ability to fulfill social roles within the family is expected; however, the extent of this social role disruption and potential impact on disease outcomes and psychological well-being may not be fully appreciated.…”
Section: Introductionmentioning
confidence: 99%